Encountering Bigotry : Befriending Projecting People in Everyday Life. - Lichtenberg, Philip (Routledge, Taylor & Francis Group, 2014)
Encountering Bigotry examines the occurrence of emotionally fraught and socially provocative expressions, such as racism, sexism, homophobia, anti-Semitism, classism, and other forms of hatred of outgroups or others, in everyday experience. The editors categorize such remarks as projections, particular forms of perceiving oneself and others in the world. This projection allows the person to perceive emotional intensity without owning (i.e., without attributing to the self) the feeling or experiencing anxiety-producing emotions. Such projections are not pathological, they observe, b.